Knowledge map and future avenue of Cognitive Literary Studies: a bibliometric analysis (1975–2024) - Qiaoqiao, Zhou; Omar, Noritah; Zainal, Zainor Izat; Bahar, Ida Baizura (SAGE Publications, 2025)
This study conducts a bibliometric analysis to address the limitations of systematic literature reviews in handling large datasets, and provides a comprehensive knowledge map and future avenues of cognitive literary studies (CLS) that have yet to be systematically explored. Utilizing VOSviewer as a quantitative tool supplemented by qualitative interpretation, this study analyzes 1,283 journal articles extracted from Web of Science Core Collection database, aiming to offer a longitudinal view of CLS’s evolving landscape. This study identifies its inception, journal and national contributions, influential scholars, and articles using citation analysis. It examines dominant research themes and predicts developing trends using co-citation and co-word analysis. This study yields the following findings: (1) CLS research began in 1975, with a notable surge from 2000 onward; (2) Poetics Today is the most influential journal, with the United States leading in academic contributions. Scholars such as Zunshine, Palmer, Fauconnier & Turner and their works are most frequently co-cited; (3) The four dominant research topics are cognitive/theoretical/ontological foundations of narrative, intersection between cognitive poetics and cognitive linguistics, affective cognition in literary studies, and extended cognition and the environment; (4) The five developing trends are the neurocognitive poetics model of literary reading, expansion of scope in CLS, second-generation approaches to CLS, neuroesthetics and literary perception, and cognitive function of imagination. This study offers a foundational profile that contributes to the consolidation of CLS as a multidisciplinary and evolving field, facilitating a more systematic understanding of the theoretical engagement and methodological innovation within the field.